Ternary Spinel MCo2O4 (M = Mn, Fe, Ni, and Zn) Porous Nanorods as Bifunctional Cathode Materials for Lithium–O2 Batteries - Mohamed, Saad Gomaa; Tsai, Yuan-Quei; Chen, Chih-Jung; Tsai, Yi-Ting; Hung, Tai-Feng; Chang, Wen-Sheng; Liu, Ru-Shi (ACS applied materials & interfaces, 2015)
The development of Li–O2 battery electrocatalysts has been extensively explored recently. The Co3O4 oxide has attracted much attention because of its bifunctional activity and high abundance. In the present study, toxic Co2+ has been replaced through the substitution on the tetrahedral spinel A site ions with environmental friendly metals (Mn2+, Fe2+, Ni2+, and Zn2+), and porous nanorod structure are formed. Among these spinel MCo2O4 cathodes, the FeCo2O4 surface has the highest Co3+ ratio. Thus, oxygen can be easily adsorbed onto the active sites. In addition, Fe2+ in the tetrahedral site can easily release electrons to reduce oxygen and oxidize to half electron filled Fe3+. The FeCo2O4 cathode exhibits the highest discharging plateau and lowest charging plateau as shown by the charge–discharge profile. Moreover, the porous FeCo2O4 nanorods can also facilitate achieving high capacity and good cycling performance, which are beneficial for O2 diffusion channels and Li2O2 formation/decomposition pathways.